1984
DOI: 10.4315/0362-028x-47.11.886
|View full text |Cite
|
Sign up to set email alerts
|

Alternaria Toxins and Their Importance in Food

Abstract: Members of the genus Alternaria are known to produce compounds that are pathogenic to plants and other test organisms, including animals. Of the more than 30 compounds produced, tenuazonic acid, alternariol, alternariol methyl ether and altertoxin I are the most toxic to animals. These toxic compounds have been isolated from diseased plant tissue and could be a problem with foods, although only tenuazonic acid has been isolated in small amounts from wholesome foods. A number of Alternaria spp. can produce thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…Although a large number of studies have been done on AOH, AME, TA and other Alternaria metabolites [King and Schade, 1984;Torres et al, 1993;Chulze et al, 1995], this is one of the first reports on the stability of the toxins in this oil seed. Only one study was reported on the incidence of AOH, AME, ATX-I and TA in wheat flour stored during 28 days at 20°C; a reduction of 30-40% of the metabolites was obtained [Stinson and Heisler, 1981].…”
Section: Resultsmentioning
confidence: 99%
“…Although a large number of studies have been done on AOH, AME, TA and other Alternaria metabolites [King and Schade, 1984;Torres et al, 1993;Chulze et al, 1995], this is one of the first reports on the stability of the toxins in this oil seed. Only one study was reported on the incidence of AOH, AME, ATX-I and TA in wheat flour stored during 28 days at 20°C; a reduction of 30-40% of the metabolites was obtained [Stinson and Heisler, 1981].…”
Section: Resultsmentioning
confidence: 99%
“…Tenuazonic acid (TeA), alternariol (AOH), alternariol methyl ether (AME) and altertoxin-I (ATX-I) are the main Alternaria mycotoxins that can be found as contaminants of food commodities. They are produced by A. alternata which is considered the most common of the Alternaria species and perhaps the most cosmopolitan fungus (King & Schade 1984, Montemurro & Visconti 1992, Scheffer 1992, Bottalico & Logrieco 1998.…”
Section: Introductionmentioning
confidence: 99%
“…The ingestion of mycotoxins, by man or animals, gives rise to disease conditions, broadly referred to as mycotoxicoses. Moulds belonging to the genus Alternaria reportedly produce over 40 mycotoxins (King & Schade, 1984).…”
Section: Introductionmentioning
confidence: 99%